2018
DOI: 10.1137/17m1129982
|View full text |Cite
|
Sign up to set email alerts
|

A Piecewise Korn Inequality in SBD and Applications to Embedding and Density Results

Abstract: We present a piecewise Korn inequality for generalized special functions of bounded deformation (GSBD 2 ) in a planar setting generalizing the classical result in elasticity theory to the setting of functions with jump discontinuities. We show that for every configuration there is a partition of the domain such that on each component of the cracked body the distance of the function from an infinitesimal rigid motion can be controlled solely in terms of the linear elastic strain. In particular, the result impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 38 publications
(152 reference statements)
3
48
0
Order By: Relevance
“…The Griffith energy (G) is approximated by the functionalŝ Ω (v + η ε )f p (e(u)) + (1 − v) 2 4ε + ε q−1 |∇v| q dx , lim ε→0 η ε ε p−1 = 0 , (G ε ) for u ∈ W 1,p u 0 (Ω; R n ) := W 1,p (Ω; R n )∩{u : tr ∂Ω (u−u 0 ) = 0 on ∂ D Ω}, v ∈ W 1,q 1 (Ω; [0, 1]) := W 1,q (Ω; [0, 1]) ∩ {v : tr ∂Ω v = 1 on ∂ D Ω}, and +∞ otherwise: such approximation has been proven without any a priori assumption on u, for any p > 1, and in any dimension in [25], together with compactness for minimisers (see [26]), assuming that O δ,x 0 (∂ D Ω) ⊂ Ω for δ ∈ (0, δ), (1.2) for some δ > 0 and x 0 ∈ R n , where O δ,x 0 (x) := x 0 + (1 − δ)(x − x 0 ). This generalises [21,22,51], assuming a priori u ∈ L 2 and p = 2, [28], requiring u ∈ L p , p > 1, and [43], obtained in dimension 2 (see also e.g. [45,18,53] for the antiplane shear case and different approximations).…”
Section: Introductionsupporting
confidence: 56%
“…The Griffith energy (G) is approximated by the functionalŝ Ω (v + η ε )f p (e(u)) + (1 − v) 2 4ε + ε q−1 |∇v| q dx , lim ε→0 η ε ε p−1 = 0 , (G ε ) for u ∈ W 1,p u 0 (Ω; R n ) := W 1,p (Ω; R n )∩{u : tr ∂Ω (u−u 0 ) = 0 on ∂ D Ω}, v ∈ W 1,q 1 (Ω; [0, 1]) := W 1,q (Ω; [0, 1]) ∩ {v : tr ∂Ω v = 1 on ∂ D Ω}, and +∞ otherwise: such approximation has been proven without any a priori assumption on u, for any p > 1, and in any dimension in [25], together with compactness for minimisers (see [26]), assuming that O δ,x 0 (∂ D Ω) ⊂ Ω for δ ∈ (0, δ), (1.2) for some δ > 0 and x 0 ∈ R n , where O δ,x 0 (x) := x 0 + (1 − δ)(x − x 0 ). This generalises [21,22,51], assuming a priori u ∈ L 2 and p = 2, [28], requiring u ∈ L p , p > 1, and [43], obtained in dimension 2 (see also e.g. [45,18,53] for the antiplane shear case and different approximations).…”
Section: Introductionsupporting
confidence: 56%
“…When L = R d×d skew , one can equivalently characterize P R L (Ω) as the subspace of GSBD functions (see [38]) whose symmetrized approximate gradient e(u) equals zero L d -almost everywhere. For a proof we refer to [36,Theorem A.1] and [48,Remark 2.2(i)]. In a similar fashion, in the case L = SO(d), P R L (Ω) coincides with the GSBV functions whose approximate gradient satisfies ∇u(x) ∈ SO(d) for L d -a.e.…”
Section: Piecewise Rigid Functionsmentioning
confidence: 96%
“…However, our primary purpose comes from the study of free-discontinuity problems defined on the space GSBD p , see [38], which has obtained steadily increasing attention over the last years, cf., e.g., [30,31,32,33,34,35,46,47,48,50]. We have indeed already mentioned before how the analysis of partition problems has proved to be a relevant tool in the study of freediscontinuity problems on SBV .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The compactness result relies on the idea that a control on a sequence of functions can always be ensured by subtracting suitable piecewise rigid motions. Using a piecewise Korn inequality [33,35], it can be shown that such a modification can be performed without essentially increasing the energy of the configurations.…”
Section: Introductionmentioning
confidence: 99%